Arctic sea ice melting has produced distinct sea ice-atmosphere coupled patterns - Wu, Bingyi (Environmental research letters, 2025)
The possible influence of Arctic sea ice on weather events and climate variations has received considerable attention, while the evolution of its relationship with interannual variations of winter temperature across much of Eurasia remains poorly understood. This study quantitatively describes two distinct coupled patterns between autumn Arctic sea ice concentration in the Barents–Kara seas and the subsequent winter regional temperature over Eurasia. The leading coupled pattern dominantly depicts interannual variations of the cold Arctic―warm Eurasia or warm Arctic—cold Eurasia configuration, differing from the background warming pattern. While the second coupled pattern describes in-phase interannual variations of winter temperature over the Arctic and across much of Eurasia. This second pattern displayed an interdecadal transition in the early 2010s, from frequent occurrences of the cold Arctic―cold Eurasia pattern to the dominant warm Arctic―warm Eurasia configuration. Through this interdecadal transition, the warm Arctic―warm Eurasia configuration replaced the leading coupled pattern. The previously proposed the tropospheric and stratospheric processes cannot fully explain this Arctic―Eurasia temperature configuration. These findings underscore the pivotal role of Arctic sea ice melting in influencing the interannual and interdecadal variations of winter atmospheric circulation patterns and have significant implications for predicting short-term winter temperature trends over Eurasia.